Design and fabrication of vegetable cutting machine / Muhammad Hakimie Md Mokhtar - Md Mokhtar, Muhammad Hakimie (2023)
Consuming vegetables for our daily routine life are good for our health benefits. Veggies contain a lot of vitamins, and it can boost up our mind. There are variety of veggies that can be eaten without cook it first. But most of it must be cooked first to get the nutritious from it. Kitchen knife was invented to help people easily cut veggies into small pieces so that they can put it in their dishes. The main problems with this tool now it is dangerous to use, lack of time and using too much energy especially for people working as chef. My objective is to invent an automatic vegetable cutting machine that can solve all of these problems and can simplify human life. During this project, I will be making a full research based on the design of the product, material selected and using mechanical engineering concept to make this project successful. After this project finished, I would be expecting this product will solve all of the main problems for the consumer of this product.